Interior design visual presentation - Mitton, Maureen (2024)
"This is one of the few titles on the market that comprehensively addresses the visual design and presentation skills of the interior designer. Featuring thorough, process-oriented coverage on the planning, layout, and the design of interior building spaces, this book is an accessible to guide to techniques for executing creative and successful design graphics, models, and presentations. Interior Design Visual Presentation, 6th Edition includes a new overview of the design process for residential and commercial real estate for students at all levels. Other revisions include new discussion of the impact of digital communication, examples of rendering materials in color, review of the latest tools for digital rendering, additional detail on creating hand drawings, and advanced technologies for physical model making. Throughout, the author highlights where material relates to the NCIDQ exams for students preparing for them"--
Includes bibliographical references and index.
Keywords: Interior decoration rendering; Interior decoration -- Design